2016
DOI: 10.1007/s11596-016-1556-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of modified nonequilibrium plasma with chlorhexidine digluconate on primary cultured human gingival fibroblasts

Abstract: The aim of this study was to investigate the cytotoxicity of modified nonequilibrium plasma with chlorhexidine digluconate (CHX) on human gingival fibroblasts (HGFs), and to evaluate the biosecurity of modified nonequilibrium plasma with 2% CHX as a new method of root canal treatment. Tissue samples taken from human gingiva were primarily cultured and passaged. Cells from passages 3-7 were used. HGFs were treated by modified nonequilibrium plasma with 2% CHX for 0 min (control group), 30 s, 1 min, 1.5 min, 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…In their study, cell viability was significantly reduced when exposed to 2% CHX for 3 minutes or longer. Similar to findings in this study, Chen et al demonstrated that cell viability was reduced in a time-dependent manner, with cells exposed to CHX for 10 minutes having cell survival rates significantly lower than the same cells exposed to CHX for only 3 minutes 21 . Flemingson et al 33 exposed cultured human fibroblasts to different dilutions of commercially available CHX anti-plaque mouthwash products (1%, 2%, 5%, 10%, 20%, and 100%) for 1, 5, and 15 minutes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In their study, cell viability was significantly reduced when exposed to 2% CHX for 3 minutes or longer. Similar to findings in this study, Chen et al demonstrated that cell viability was reduced in a time-dependent manner, with cells exposed to CHX for 10 minutes having cell survival rates significantly lower than the same cells exposed to CHX for only 3 minutes 21 . Flemingson et al 33 exposed cultured human fibroblasts to different dilutions of commercially available CHX anti-plaque mouthwash products (1%, 2%, 5%, 10%, 20%, and 100%) for 1, 5, and 15 minutes.…”
Section: Discussionsupporting
confidence: 89%
“…In a study by Cline et al 29 , CHX was shown to affect fibroblast proliferation and impair cell adhesion. Chen et al 21 . exposed human gingival fibroblasts to 2% CHX and used the CCK assay to determine cell survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Data presented in this study confirmed that immobilization of CHX on MNPs also decreases the toxic effect of CHX without affecting its killing properties. In effect, magnetic derivatives of CHX may be an interesting alternative for formulations presented by Chen et al 60 Importantly, the employment of nanotechnology-based structures in dentistry provides a way for the introduction of novel therapy approaches based on structures that allow to control drug release and to improve the regenerative processes with subsequent strong antimicrobial activity, even in the presence of salivary proteins. …”
mentioning
confidence: 99%
“…The cultured cells from gingiva were tested by immunocytochemical analysis. These cells were tested negative for anti-keratin staining whilst staining positive for vimentin, suggesting these cells to be gingival fibroblasts (23). Cells between sixth and ninth passages were used for the assessment of cell cytotoxicity.…”
Section: Methodsmentioning
confidence: 99%